Penerapan Sistem Informasi Penjualan Produk Skincare Merek Aftermyskin dengan Metode CRM pada Toko Aftermyskin di Kota Bandar Lampung - Zidane, Ahmad Rifqi; Samsugi, S. (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to develop a web-based sales information system for AFTERMYSKIN Cosmetic Store that integrates Customer Relationship Management (CRM) methods. The system is designed to simplify transaction management and expand product promotion. Data collection was carried out through interviews with the store owner and literature review. The system development follows the Waterfall method, which includes requirements analysis, design, coding, testing, and implementation. The system is built using PHP, the CodeIgniter 3 framework, and a MySQL database. The results indicate that the implementation of CRM in this system enables the store owner to manage customer data more effectively, understand their preferences, and provide more accurate product recommendations. This system is expected to improve operational efficiency and strengthen customer relationships, which will positively impact sales and customer satisfaction.